Effects of nano-silica treatment on the flexural post cracking behaviour of polypropylene macro-synthetic fibre reinforced concrete. (March 2018) - Di Maida, Pietro; Sciancalepore, Corrado; Radi, Enrico; Bondioli, Federica
Highlights: We improved bonding properties of synthetic macro fibres by nano-silica treatment. Sol-gel reactions promote the growth of colloidal particles. We explored the morphological changes in the ITZ of PP fibres by SEM. We performed three-point bending tests on notched MSFRC beam specimens. Increasing in concrete toughness and residual post-cracking strength was recorded. Abstract: The effects of a surface nano-silica treatment, carried out with the sol gel method, on the post-cracking behaviour of polypropylene macro-synthetic fibre reinforced concrete are experimentally investigated here for the first time. The present study extends previous experimental and analytical investigations on the corresponding improvement of the bonding properties of a single synthetic macro fibre, performed by means of pull-out test. Scanning electron microscopy is adopted here to explore the changes in the morphological characteristics of polypropylene macro synthetic fibres, before and after mixing in the concrete matrix. A comparative analysis, carried out with three-point bending tests on notched beam specimens, is used to evaluate the effects of the nano-silica treatment on the concrete post cracking behaviour. Increase in concrete toughness and residual post-cracking strength is recorded due to improved adhesion between fibres and the concrete matrix and to the consequent increase in the frictional shear stress generated during the fibre pull-out, especially for large crack opening. As shown by the SEM images, the nano-treatment favours the bonding of the concrete hydration products to the surface of the treated fibres, thus ensuring strengthening of the interface transition zone. In addition, the links between the nano-silica coating and the concrete hydration products improve the frictional shear stress and thus the overall energy absorption, as denoted by the increase of the residual strength during the post-cracking phase.